Antidepressant Efficacy of Nutraceutical Gummies: Formulation of Withania Somnifera and Valeriana officinalis Evaluated in Force Swim Test Model - Mann, Parvinder; Sharma, Uddeshya; Singh, Gurvirender; Jangra, Geeta (Recent Advances in Food Nutrition & Agriculture, 2025)
<span class=
Keywords: depression